Scheduled flight control system of tilt-rotor VTOL PAV - Kang, Namuk; Whidborne, James F.; Lu, Linghai; Enconniere, Julien (American Institute of Aeronautics and Astronautics (AIAA), 2023)
This paper develops the longitudinal flight control scheme for the tilt-rotor VTOL Aston Martin Volante Vision. It is envisaged that the aircraft will be flown by a "flight-naive pilot" who is less well-trained than normal. The conversion corridor is developed and the optimum tilt schedule is determined using the minimum power curve and numerical optimisation to encompass hover, conversion and cruise flight without manipulating the rotor tilt angle. The methodology is found to be unique because two conversion schedules were integrated to reflect critical factors for conversion and stationary configurations. A proportional-integral-derivative (PID) controller has been designed with a suitable inceptor response and control allocation for a flight-naïve pilot while a blending schedule has unified different response types at the low and high speed into a single control system. The PID controllers are evaluated using design guidelines of ADS-33E-PRF and MIL-STD-1797A. The conversion flight simulation shows that the suggested longitudinal stability and control augmentation system (SCAS) are expected to reduce the pilot workload and improve handling qualities making performance and handling more suitable for a flight-naive pilot.